Echocardiography: Is there unseen risk in cardiac ultrasound? - Herbst, Philip (SA Heart Journal, 2017)
The biological safety of medical ultrasound, including echocardiography is undisputed. However, the performance of medical ultrasound requires a significant amount of interpretation on the part of the operator who must be aware and continuously mindful of the many pitfalls inherent in the imaging modality and this is particularly true of echocardiography. A considerable amount of training is required to learn how to perform echocardiography at a safe, let alone high, standard. The echocardiographer requires a sound knowledge and awareness of the pitfalls of the technique and an understanding of the clinical conditions being evaluated.